Results of a Discussion on the State of Experimental Archaeology in Switzerland - T. Doppler; Stefanie Osimitz; Kathrin Schäppi (EXARC Journal, 2012)
The ‘Pfahlbauland’ exhibition at Landiwiese in Zurich in 1990 was an important event for the Swiss experimental archaeology community. On 27 March 2010, the board of the Working Group on Experimental Archaeology in Switzerland (AEAS-GAES) invited a panel of experts to hold a public debate in Olten on whether the incentives that had existed at the time still played their part, how they were now constituted and what the future perspectives were.